Factors associated with acquisition of human infective and animal infective trypanosome infections in domestic livestock in Western Kenya - Wissmann, B. von; Machila, N.; Picozzi, K.; Fèvre, Eric M. (Public Library of Science, 2011)
Trypanosomiasis is regarded as a constraint on livestock production in Western Kenya where the responsibility for tsetse and trypanosomiasis control has increasingly shifted from the state to the individual livestock owner. To assess the sustainability of these localised control efforts, this study investigates biological and management risk factors associated with trypanosome infections detected by polymerase chain reaction (PCR), in a range of domestic livestock at the local scale in Busia, Kenya. Busia District also remains endemic for human sleeping sickness with sporadic cases of sleeping sickness reported.